INFLUENCES OF ATORVASTATIN USE ON SYSTEMIC INFLAMMATION AND ADIPOKINE PROFILE IN ABDO-MINALLY OBESE PATIENTS AFTER LACUNAR STROKE - Delva, M. (World of Medicine and Biology, 2013)
We have studied the effects of post-stroke intake of atorvastatin (20 mg per day for 90 days) on systemic inflammation as well as circulating adiponectin and leptin levels in abdominally obese (class 2 obesity) patients with acute ischemic lacunar stroke. Atorvastatin use led to significant reduction of post-ischemic inflammatory response on 10th day after stroke (in form of decreased C-reactive protein, tumor necrosis factor-α, monocyte chemoattractant factor-1 and interleukin-6 levels). Atorvastatin treatment was associated with reduced level of chronic systemic inflammation on 90th post-stroke day (decreased C-reactive protein level). Atorvastatin use doesn’t impact on leptin blood level, but was associated with significant increase in circulating adiponectin on 10th day after stroke.
Keywords: abdominal obesity; lacunar stroke; atorvastatin; systemic inflammation; adiponectin; leptin